Symmetrical Cascaded Switched-Capacitor Multilevel Inverter Based on Hybrid Pulse Width Modulation - Lingling Cao (MDPI AG, 2021)
Multilevel inverters have been widely used in various industrial applications such as renewable energy generation and electric vehicles. An improved circuit of symmetrical cascaded switched-capacitor multilevel inverter is proposed so that the reactive power is absorbed by its power supply instead of capacitors. Then, a special hybrid pulse width modulation strategy combing level-shifted pulse width modulation (LS-PWM) and phase-shifted pulse width modulation (PS-PWM) was developed for the inverter. With this modulation algorithm, the power between cascaded units is automatically balanced, and the voltage of the capacitor in each unit is also automatically balanced to the dc input voltage. In addition, the optimized capacitor voltage ripple makes it possible to use a smaller capacitor to produce a better output voltage waveform. Theoretical analysis, simulation and experimental results show that the equivalent switching frequency of the cascaded multilevel inverter is twice the original frequency so that the output voltage harmonics are only distributed near even multiples of the carrier frequency.